Library anxiety its relationship to computer anxiety and library use among freshman students of De La Salle University-Dasmariñas in Cavite - Caraballa, Jerome M.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
A visit to the library may prove to be an inevitable activity to a college student whether he may like it or not. It is because, library use among students is an essential part in any student's life to succeed not only in school but also in our society. Of course, not all students are properly equipped with all the knowledge especially when using a library that exhibits state-of-the-art facilities, like the one in De La Salle University - Dasmarinas, Cavite. The Aklatang Emilio Aguinaldo, as the library is called, housed and ever-expanding collection of books, journals, magazine, videos, CD-ROMS and all sorts of instructional materials. Its computers can access the World Wide Web and has its own Online Public Access Catalog (OPAC) System. All of this may be a bit overwhelming to a student, especially to a freshman, when he feels like he is not capable of handling such information. He becomes apprehensive in using the library and all of its facilities and related services like computers and such. This is called library anxiety.
The study focuses on library anxiety and its relationship to computer anxiety and library use among freshmen students of De La Salle University - Dasmarinas in Cavite.
A total of 358 randomly selected freshmen students were asked to answer a 6-page written survey questionnaire to determine their level of library anxiety. The questionnaire also aimed to measure the level of computer anxiety and library use among the respondents. By using a modified Library Anxiety Scale, it aimed to find out how the students feel about using the library to the fullest with the least amount of tension, fear or apprehension. The results indicated that freshmen students have a fair amount of library anxiety.
A modified Computer Anxiety Scale tried to determine the level of computer anxiety among the freshmen students. Even though several studies show that computers have become an integral part of the educational setting, some students still feel anxious about using it inside the library. The results indicate that freshmen students of De La Salle University - Dasmarinas, Cavite have a fair amount of computer anxiety. And it has a weak positive significant relationship with library anxiety. This result means that as the level of library anxiety increases, the level of computer anxiety also increases, and vice versa.
The data gathered from the survey questionnaire also revealed that relationship of library anxiety and frequency of library use was not significant among the freshmen students of De La Salle University - Dasmarinas, though their "comfortability" while inside the library plays a vital role on how often they visit.
Also, with the relationship of computer anxiety and frequency of library use among the freshmen students, the study revealed that it was not significant even though computers are an indispensable part of the society.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Aklatang Emilio Aguinaldo; De La Salle University -- Dasmariñas, Cavite -- Freshmen; Computer anxiety -- Philippines -- Cavite; Library anxiety -- Philippines -- Cavite